Retromolar Embryonal Rhabdomyosarcoma: A Case Report - Johanna, Caryl Augustine; Setiawan, Gede Budhi (JBN (Jurnal Bedah Nasional); Vol 1 No 2 (2017): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2017.v01.i02.p03, 2017)
Background: embryonal rhabdomyosarcoma is common of rhabdomyosarcoma, usually in 5 years old child. Approximately 28% of embryonal rhabdomyosarcomas occur in head and neck area, and 0.04% of cases occur as intra-oral tumors. Case: a 13 years old female complained of a firm and painless progressive mass in her right mandibular retromolar 6 months prior to her current medical check-up. There was a reddish 8x5 cm mass on the right posterior mandibular region. Mid face CT scan showed a well-bordered solid mass in her right oral cavity expanding to the right maxilla without bone destruction nor intracranial expansion. Incisional biopsy concluded the morphology as an embryonal rhabdomyosarcoma. Four series of neoadjuvant chemotherapy of vincristine, adriamycin, and cyclophosphamide (VAC) regimen gave partial response clinically and was followed by right marginal mandibulectomy procedure. Histopathological surgical specimen examination showed no active cancer cells. Adjuvant chemotherapy was given afterward. The result is good cosmetically and functionally. Discussion: retromolar embryonal rhabdomyosarcoma is diagnosed by physical examination of progressive and firm retromolar mass, retromolar mass with or without nearby-structures invasion radiologically, and confirmed by histopathology examination. Neoadjuvant chemotherapy showed partial response clinically. Complete tumor resection with adequate surgical margin is the key for a successful therapy. Conclusion: embryonal rhabdomyosarcoma is rare. The treatment plan and outcome are unique in every patient depending on the location of the tumor, the histological type, and the respectability. Pathological examination and CT scan play a significant role in diagnosing and making a good surgical plan. Early diagnosis and complete resection with adequate surgical margin is the key for a successful therapy.